Second Career Teachers: Work Motivations - Nancy H. Ellis (Educational Considerations, 1993)
Although attention has been focused on the projected teacher shortage caused by the lack of bright young people entering the teaching profession, little has been written about those people who leave positions in other professions to pursue teaching as a second career.